Testing a model of UK growth: A causal role for R&D subsidies - Lucy Minford; David Meenagh (Cardiff University, Cardiff Business School, 2018)
We show that a DSGE model in which subsidies to private sector R&D stimulate economic growth, following the predictions of semi-endogenous growth theory, can account for the joint behaviour of UK output and total factor productivity for 1981-2010. R&D subsidies are measured as government-funded R&D performed by the private sector as a proportion of total private sector R&D. We estimate and test the performance of the model using Indirect Inference, and also investigate the robustness of the results using a Monte Carlo exercise. Our findings indicate that sharp cuts in R&D subsidies tend to have highly persistent growth effects in the UK.
Keywords: E00; O00; O38; O50; 330; R&D; subsidies; economic growth; government policy